Sun Yatsen, Robert Wilcox and Their Failed Revolutions, Honolulu and Canton 1895 - Anderson, Patrick, 1966- author.
1 online resource (xiv, 508 pages).
Keywords: Dynamite on the Tropic of Cancer is the radical, explosive retelling of the first decade of the 'Father of Modern China' Dr Sun Yatsen's globally shaped formation as a professional revolutionist, and of the impact of the adult Sun's revolutionary relationship with Hawaiʻi and with his varied communities of supporters there during its own most turbulent political decade, the 1890s, years in which this remote island nation transformed from native monarchy, via sovereign independent republic, to become the USA's first overseas territory. Drawn from neglected primary sources, Dynamite reveals the hitherto untold story of the secret revolutionary alliance forged in Honolulu's backstreets between Sun's Xingzhonghui and the idiosyncratic italophile soldier Robert Wilcox, "Hawaiʻi's Garibaldi" and leader of the Kanaka/Native Hawaiian counterrevolution of January 1895. This failed uprising to restore Hawaiʻi's tragic last Queen, witnessed firsthand by Sun Yatsen, became the archetype upon which ten months later Sun would base his own first attempt at armed insurrection in China: the Canton uprising of 26 October 1895. With an epic sweep across the Pacific's Tropic of Cancer, Dynamite is the most important study yet written on the origins of Sun Yatsen's Chinese Revolution and its dynamic interface with Hawaiian history.